The Shifting of Function and Role of the Leader in the Matrilineal Kinship System in Minangkabau in the Performing Arts of Ratok Nagari - Nurwani Nurwani; Martozet Martozet; Yunaidi Yunaidi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Minangkabau has undergone changes in various fields including customs related to the role and function of the Penghulu. These changes greatly affect life in the kinship system in Minangkabau. This study aims to see the phenomenon of changing the role and function of the Penghulu and its influence in the life of the matrilineal community, which is interpreted and expressed in the artwork of Ratok Nagari. In order to know the shift in roles and functions, the theory of change is used. Social change is closely related to people's lives, resulting in changes in the values and order of community life. This research uses qualitative methods including literature review, observation, interviews, and documentation. While the method of creationincludes exploration, improvisation and formation.The leader has a very important position, seen from his role and function in determining the future of his people.The shifting of times and interests have made lines of society reap controversy in living social life. The lack of reviewing and maintaining the Nagari adat traditions makes a group of people forget the function and role of the Penghulu. Currently the Penghulu is no longer carrying out its role and function as a leader in the matrilineal, tribal and Nagari families, in accordance with the Nagari customs they lead. The process of creating Ratok Nagari begins with interpreting the phenomena that have occurred in the changing roles and functions of the Penghulu, followed by reinterpreting the creation of dance concepts. The creation of a dance work entitled Ratok Nagari is a reflection of the worker's reflection in seeing and responding to the Minangkabau social phenomenon.